Knowledge and awareness of emergency department residents and physicians regarding the management of dentofacial traumatic injuries: a cross-sectional study - Tahoora Yousuf; Muhammad Subhan Khan; Robia Ghafoor (Nature Publishing Group, 2024)
Abstract Background Majority of patients with Dento-Facial Traumatic Injuries (DFTI) seek initial care at an Emergency Department (ED). The timely management of DFTI is of utmost importance in determining long-term prognosis of the tooth and the patient's overall quality of life. Thus, knowledge and awareness of ED residents & physicians regarding the management of DFTI is crucial for better patient outcomes. Numerous studies have investigated the knowledge of ED specialists regarding initial management of dental trauma, however, scientific evidence in this domain is scarce in our region. Objective The aim of this study was to evaluate the knowledge and awareness of ED residents and physicians regarding diagnosis and management of DFTI using a web-based survey on REDCap. Methods An observational cross-sectional study was conducted among the ED residents and physicians of private and public hospitals in Karachi, Pakistan. Data was collected through a web-based questionnaire, sent via email to the participants. The survey comprised of questions assessing their knowledge regarding the diagnosis and management of various dental and maxillofacial injuries. Responses from the participants were graded as low, moderate or high knowledge levels according to a pre-determined criteria. Pearson's chi-square test was applied to determine the association between knowledge scores. Results The total response rate was 47.6%. Out of 116 participants, 49 (42%) responses were received from physicians and 67 (58%) from residents. The overall knowledge level of participants was low (46.6%) and there was no significant difference in the knowledge level between residents and physicians (p = 0.157). Participants who had received formal training in dental trauma (p = 0.038) and those with more years of clinical experience (p = 0.004) had higher knowledge scores, that were statistically significant. Conclusions The knowledge and awareness of ED residents and physicians in dental trauma management was generally low. Specialized training courses are required to provide timely and adequate management of traumatic dental injuries in order to improve patient-related outcomes.